Protestant autobiography in the seventeenth-century anglophone world - Lynch, Kathleen (Oxford : Oxford University Press, 2012)
This book provides a new view of the historical conditions and methods by which godly communities turned personal experience into an authorizing principle. A broad range of life-writing is explored, including Augustine's Confessions, John Bunyan's Grace Abounding to the Chief of Sinners, and Richard Baxter's Reliquiae Baxterianae.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Protestant converts -- English-speaking countries -- Biography -- History and criticism; Protestantism -- English-speaking countries -- History -- 17th century -- Sources